PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS 3D PAGEFLIP PROFFESIONAL DALAM MATA PELAJARAN MATEMATIKA KELAS IV SEKOLAH DASAR NEGERI 62 BAYANG - Yakob Zeno; Yulis Jamiah; Asriah Nurdini (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2022)
This study aims to develop professional 3d pageflip learning media on geometric materials for class IV SDN 62 Bayang. this type of research is research and development (R&D). The development model used is the ADDIE model. the research was passed only up tothe implementation stage. The results of the assessment by media experts averaged 4,5 valid criteria. the results of the leraning design expert's assessment averaged 4,3 with criteria valid. the results of the material expert's assessment averaged 4,33 with valid criteria. the average teacher response is 4,40 with very interesting criteria. then results of student responses in small group trials obtained anaverage of 73,96% with attractive criteria, while field trials obtained anaverage of 76,8% with attractive criteria. the results for the effectiveness of student learning outcomes in the small group test obtained N-Gain results of 0,48 in the medium category while student learning outcomes in the field trial N-Gain were 0,59 in the moderate category. thus pageflip professional 3d learning media in learning mathematics can be used in the learning process.